(untitled) (Web of Teachers: Inderscience Research, 2024)
This article is devoted to distance learning using modular learning technology in teaching physics, which lists the advantages and disadvantages of modular technology, including, first of all, with each student individually. The key role is played by the ability to work independently the tasks given by the teacher allow students to independently complete tasks, creatively approach work, learn how to effectively use computer technology and the Internet, physical processes, the ability to observe on a computer monitor and use virtual experiments and virtual laboratory work when performing laboratory work and other important issues.